Chapter: 'Norway: Public Debate and the Management of Petroleum Resources and Revenues' from book: Public Brainpower: Civil Society and Natural Resource Management - Indra Overland (Palgrave Macmillan, 2017)
This chapter assesses the importance of civil society involvement and public debate for Norwegian petroleum governance. It finds that during the early years of the country's oil and gas development, the most important choices were made by a small number of decision-makers in government with little input from the rest of society. The attitude of government officials was therefore decisive for Norway's early successes. During the two first decades of Norway's petroleum era, also economists at the Ministry of Finance, the Norwegian School of Economics, Statistics Norway and the University of Oslo played important roles. One of the greatest successes of Norwegian oil and gas governance, the sovereign wealth fund, was created by technocrats in interaction with politicians. However, over time, and in a way similar to the Netherlands, civil society and public debate came to play more influential roles. What characterizes contemporary Norwegian petroleum governance is that it has many legs to stand on: an active and diverse civil society, free and diverse media, many political parties representing differing interests, numerous institutions of research and higher education and, importantly, a strong technocracy inside and outside government. In combination, these legs provide for both reliability and dynamism as Norwegian petroleum governance evolves. Finally, a key aspect of Norway's Nordic model is constant compromise-which is difficult to achieve in more polarized societies.